2018
DOI: 10.2967/jnumed.118.211102
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Serial 18F-FDG PET and 18F-Fluoride PET to Predict Time to Skeletal-Related Events, Time to Progression, and Survival in Patients with Bone-Dominant Metastatic Breast Cancer

Abstract: Assessing therapy response of breast cancer bone metastases is challenging. In retrospective studies, serial F-FDG PET was predictive of time to skeletal-related events (tSRE) and time to progression (TTP).F-NaF PET improves bone metastasis detection compared with bone scanning. We prospectively tested F-FDG PET andF-NaF PET to predict tSRE, TTP, and overall survival (OS) in patients with bone-dominant metastatic breast cancer (MBC). Patients with bone-dominant MBC were imaged withF-FDG PET and F-NaF PET befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…High PSMA PET uptake in areas suspicious for metastasis is considered highly reliable for prostate cancer and discordance with NaF can be interpreted to suggest there is an invasive component not driven by osteoblastic reaction. This parallels bone findings in metastatic breast cancer, where predominately osteolytic mechanisms are suspected to underlay observed discordance between NaF PET/CT and FDG PET/CT [25, 26].…”
Section: Discussionsupporting
confidence: 73%
“…High PSMA PET uptake in areas suspicious for metastasis is considered highly reliable for prostate cancer and discordance with NaF can be interpreted to suggest there is an invasive component not driven by osteoblastic reaction. This parallels bone findings in metastatic breast cancer, where predominately osteolytic mechanisms are suspected to underlay observed discordance between NaF PET/CT and FDG PET/CT [25, 26].…”
Section: Discussionsupporting
confidence: 73%
“…In general, a negative [ 18 F]-NaF-PET/CT can be used to exclude bone metastases, but in case of positive findings, [ 18 F]-NaF-PET/CT should be carefully interpreted and correlated with CT findings. With regard to the prognostic value of [ 18 F]-NaF-PET/ CT, one prospective study was performed in 28 BC patients with bone-dominant disease, showing no correlation between baseline SUV max and skeletal-related events, time-to-progression or overall survival (OS) [41]. However, ΔSUV max of 5 lesions between baseline and 4 months of systemic treatment was associated with OS [41].…”
Section: Clinical Validitymentioning
confidence: 99%
“…With regard to the prognostic value of [ 18 F]-NaF-PET/ CT, one prospective study was performed in 28 BC patients with bone-dominant disease, showing no correlation between baseline SUV max and skeletal-related events, time-to-progression or overall survival (OS) [41]. However, ΔSUV max of 5 lesions between baseline and 4 months of systemic treatment was associated with OS [41]. With regard to the predictive value of [ 18 F]-NaF-PET/CT, two small studies showed that lack of endocrine treatment efficacy was related to an increase in metabolic flux to mineral bone or SUV max in BC patients with bone only disease (see Table 1) [42,44].…”
Section: Clinical Validitymentioning
confidence: 99%
“…Finally, response assessment can be difficult in certain settings regardless the therapy given. In a bone-dominant disease such as prostate cancer and hormone-positive breast cancer, response assessment is hampered as bone lesions are considered non-evaluable by RECIST [5].…”
Section: Introductionmentioning
confidence: 99%